Determining the influence of barrel length on the ballistic characteristics of hunting cartridges - Golub, Victor; Bisyk, Serhii; Golub, Gennadii; Zozulevych, Ihor; Kuprinenko, Oleksandr; Davydovs’kyi, Leonid; Sedov, Sviatoslav; Aristarkhov, Oleh (Eastern-European Journal of Enterprise Technologies, 2026)
A hunting rifle with a variable barrel length has been examined in this study. The task addressed was to determine the ballistic indicators of hunting cartridges for different barrel lengths. A standard deviation in shot distribution on the target and the area of damage by hunting cartridges depending on the length of the hunting rifle barrel were established. The influence of barrel length on the ballistic characteristics of hunting cartridges was investigated by conducting a multifactorial experiment according to the D-optimal Box-Behnken plan. As a result of experimental studies, it was found that the maximum value of standard deviation in shot distribution at the level of 21 cm is achieved with a barrel length of 150 mm and a shot charge mass of 36 g. At the same time, the gunpowder charge did not have a significant effect on the standard deviation in shot distribution on the target. The standard deviation of shot distribution has maximum values when the powder charge is maximum while the shot mass is minimum. The area of damage was modeled by increasing the penetration point on the target to the size of the total equivalent diameter of the most vulnerable elements of unmanned aerial vehicles (UAVs) with FPV (First-Person View) piloting. On a target with an equivalent diameter of 8 cm, the area of damage has a maximum value of 1.2 m2 with a barrel length of 150 mm, a powder charge mass of 2.28 g and a shot charge mass of 54 g. Reducing the mass of the shot charge and the mass of the powder charge leads to a decrease in the area of damage at any barrel length. The practical significance of the results is that they could be applied to improve cartridges and individual means of defeating UAVs with FPV piloting. In addition, they might be used in automatic protection systems that are promising for installation on combat vehicles